Passport fixing 1 ; Cars Orbos Bill ; The art of mime [videorecording] - Lazaro, Cheche (The Probe Team, 1988)
An investigative report on how fake passports can be bought for a fee; Looks at the high costs of cars and the proposed bill by Congressman Orbos ; Marcel Marceu, a mimist and a legend, a profile of the artist.